The death of communal liberty : a history of freedom in a Swiss mountain canton - Barber, Benjamin R., 1939-2017 (Princeton, New Jersey : Princeton University Press, 1974)
Switzerland today is faced with a profound dilemma-its village life is dying, a casualty of the collision between communal norms and the need for national survival in an industrial, urbanizing world. Benjamin Barber traces the origins and evolution of communal liberty in the group of alpine villages that make up modern Canton Graubunden, and recreates their poignant thousand-year struggle to maintain this tradition in the face of a hostile environment, hierarchical feudal institutions, and European power polities. Originally published in 1975. The Princeton Legacy Library uses the latest pr.
CHAPTER VIII. Communal Autonomy and Swiss Federalism CHAPTER IX. The Confrontation with Modernity; BIBLIOGRAPHY; INDEX.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Graubünden (Switzerland) -- History; Grisons (Suisse) -- Histoire; SOCIAL SCIENCE -- Sociology -- General; Switzerland -- Graubünden; History